Smart Grid and Computer Network: How Analogous Are They? - Khalid Lefrouni; Rachid Ellaia (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Technological advances allowing optimal exploitation of renewable energy sources and the development of new information and communications technology (ICT), have led to the appearance of a new network so-called Smart Grid. This article is dedicated to the study of similarities and differences between the smart grid and the computer network, thus, in order to better carry out this comparison. Firstly, we present the structure, operational model and benefits of smart grid. Secondly, we identify analogous quantities and similar parameters between the two networks. DOI: http://dx.doi.org/10.11591/telkomnika.v15i1.8087